Molecular prognostic factors in early-stage cervical adenocarcinoma - Bodzek, Maciej; Blecharz, Paweł; Ryś, Janusz; Szatkowski, Wiktor; Jasiówka, Marek; Majchrzak, Paweł; Halaszka, Krzysztof; Kruczak, Anna; Lackowska, Bożena (Polish Journal of Pathology, 2018)
Within the past years the proportion of cervical adenocarcinomas has increased, however, there is a shortage of data regarding immunohistochemical and molecular features and their prognostic relevance in early-stage cervical adenocarcinoma (esCAC). Aim of the present study was to evaluate molecular prognostic factors in esCAC patients treated with primary surgery. Analyses of surgical specimens in 59 patients with esCAC were performed on fixed paraffin-embedded sections of tumour tissue. Tumour tissue sections were routinely stained with hematoxylin and eosin followed by microscopic examination. Immunohistochemical analyses (IHC) were performed on paraffin-embedded section. Flow cytometry (FCM) analysis of paraffin-embedded tumor tissue was performed using flow cytometer FACSCalibur equipped with argon laser. DNA histogram analysis was performed with ModFit application. Treatment effectiveness was evaluated using overall 5-year survival. Survival probability was estimated using the Kaplan-Meier method. Overall survival rate estimated using Kaplan-Meier method was 74.6%. Among the IHC and FCM features univariate analysis showed statistical significance of nm23-H1 gene expression and total S-phase fraction ≤ 11.9% (S-TOT). In multi- variate analysis LVSI and parametrial involvement had significant, negative impact on survival (HR = 8.04, p < 0.003 and HR = 4.03, p < 0.017, respectively). However, none of the tested IHC and FCM features had any influence on overall 5-year survival.